The Centenary revisited: A German traveller in Colombia's national festivities (1910) (2021)
The Centenary of the Independence of Colombia, celebrated in 1910 has recently been revisited by Colombian historiography. Within the framework of the bicentennial celebrations of the independence between 2010 and 2019, the proliferation of articles and books that deal with the subject or specific aspects of it has been considerable. Nevertheless, the great majority of the studies are based on official documents and the press of the time, thus, their judgment regarding the impact and the reception of the event are limited. By means of a new source - the travel chronicle of the German publisher, Konrad Beisswanger-an alternative perspective is offered to the interpretation and significance of the centenary independence celebrations in Bogotá. Although Beisswanger's chronicle has a political and ideological bias; its factual veracity and detailed descriptions make it a valuable document for the study of the centenary. In addition, it forces us to reflect on the use and the interpretation of the sources used in historiography that has recently been produced on the subject.